A New Model Incorporating Leadership and Institutional Factors as Mediating Variables in Regional Endogenous Growth - Robert J Stimson; Roger R. Stough (European Regional Science Association (ERSA), 2004)
Theories and approaches to endogenous growth and regional development tend to neglect or at best underplay the role of leadership and the way institutional factors are considered is usually simplistic. This paper builds on work the authors have been developing over the last year or so to develop a model framework of regional economic development that explicitly incorporates leadership and institutional factors along with the consideration of resource endowments and market fit and of entrepreneurship. An approach to operationalizing the model is proposed.
Keywords: 330